Computational modeling and parametric study of pile groups - Lazarini, Mariana (2021)
Geotechnics and the study of the behavior of soil with the construction inserted in it is of extrema importance. This study aims at the computational analysis of a group of three rein- forced concrete piles with axial and horizontal loads. The piles were inserted in non-cohesive soil (medium and dense sand). The geometric parameters of the piles (diameter, distance be- tween them, and length) and physical parameters of the soil (stratification and angle of fric- tion between them) were varied. The GEO5 "Pile Group" program, the NAVFAC DM 7.2 method was used to determine the bearing capacity. The Poulos & Davis (1980) and FEM methods for settlement, and the p-y method (FEM) to determine the internal forces distribu- tion. The efficiency of the piles is more sensitive the more the distance between them varies. For settlement, Poulos & Davis values are sensitive to distance and diameter, and in FEM they are more sensitive to diameter and length variation.